The Unresolved Design Issues in Malaysian Prefabricated Housing and Their Corrective Steps - Ahmad, Abdul Jalil; Fadhilah, Binti Md Fazil; Dayang Afiqah, binti Abang Mohamad Shibli; Joy Natalie, Cotter (Springer, Singapore, 2023)
Globally, prefabricated housing has been successful but in Malaysia, tremendous challenges still happening. We still face design issues which hinders industry to maximize the benefits of prefabricated concept. Research proves that we still practice improper way of design, where the drawings preparation is similar to conventional method, only convert into prefabricated design at mid-level. As a result, prefabricated housing cannot achieve its full advantages, thus many regard it as just to meet the government agenda. Many studies reported that the current design in prefabricated housing has no much different to conventional, thus lead to payment dispute, delay, contractual arguments, design clashes, rivalry relationship, and loopholes in warranty and insurance. Many also presume that prefabricated housing brings heavier risk than conventional housing. In this research, questionnaire surveys were distributed to address this issue, and the result was then verified through in-depth interviews with experts. Respondents consist of developers, contractors, prefabricated manufacturers, installers, architects, quantity surveyors, and engineers. The finding reveals the root problems on how and why the current design cannot meet prefabricated optimization. The contribution of this study is it highlights the main causes of design problems and suggests solutions that ensure prefabricated housing to reap maximum benefits.